Eastern Mediterranean metallurgy and metalwork in the second millennium BC : a conference in honour of James D. Muhly : Nicosia, 10th-11th October 2009 - Kassianidou, Vasiliki; Papasavvas, Giōrgos; Muhly, James David (Oxbow Books, 2012)
"Contains twenty-three papers on Cypriot and Mediterranean archaeology that compare and contrast the material culture associated with metallurgical workshops, as well as discussing technological issues and their cultural and archaeological contexts"--Provided by publisher.